Effectiveness of urea in enhancing the extractability of 2,4,6-trinitrotoluene from chemically variant soils - Das, Padmini K.; Sarkar, Dibyendu; Punamiya, Pravin; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2013)
One of the major challenges in developing an effective phytoremediation technology for 2,4,6-trinitrotoluene (TNT) contaminated soils is limited plant uptake resulting from low solubility of TNT. The effectiveness of urea as a solubilizing agent in increasing plant uptake of TNT in hydroponic systems has been documented. Our preliminary greenhouse experiments using urea were also very promising, but further characterization of the performance of urea in highly-complex soil-solution was necessary. The present study investigated the natural retention capacity of four chemically variant soils and optimized the factors influencing the effectiveness of urea in enhancing TNT solubility in the soil solutions. Results show that the extent of TNT sorption and desorption varies with the soil properties, and is mainly dependent on soil organic matter (SOM) content. Hysteretic desorption of TNT in all tested soils suggests irreversible sorption of TNT and indicates the need of using an extractant to increase the release of TNT in soil solutions. Urea significantly (p < 0.0001) enhanced TNT extraction from all soils, by increasing its solubility at the solid/liquid interface. Soil organic matter content and urea application rates showed significant effects, whereas pH did not exert any significant effect on urea catalysis of TNT extraction from soil. The optimum urea application rates (125 or 350 mg kg−1) for maximizing TNT extraction were within the limits set by the agronomic fertilizer-N rates used for major agricultural crops. The data obtained from this batch study will facilitate the optimization of a chemically-catalyzed phytoremediation model for cleaning up TNT-contaminated soils.
Keywords: TNT; Urea; Adsorption; Desorption; Solubilizing agent